10-26-92 - Boccherini's Coffee House (Albany) - Linn-Benton Community College; L. Wallace (2018)
Images 5 and 16 were used in Volume 24, Edition 4:http://libarchive.linnbenton.edu/concern/newspaper_issues/vt150j31m?locale=en